ANALISIS ATAS DIKETAHUINYA CACAT YURIDIS PADA AKTA JUAL BELI TANAH DAN RUMAH YANG DIBUAT OLEH PPAT (PUTUSAN MAHKAMAH AGUNG NO. 2333 K/PDT/2015) - DONA CHRISTIN (PREMISE LAW JURNAL, 2017)
buy and sell agreement has to meet 4 (four) eligibility requirements of an agreement, which is stipulated in Article 1320 of the Civil Code; namely, a binding consensus, a capability of making an agreement, a particular thing, and a legitimate (according to the Islamic Law) or allowable cause. Furthermore, buy and sell of land must also fulfill the elements of material and formal requirements. Material requirements regulates the subject and object of the deal in which the seller and buyer are the rightful owners of the land sold and the object is not in a dispute. The formal requirement is when all material requirements are fulfilled, then according to PP (Governmental Regulation) No. 24/1997 on Land Registration as required by UUPA, require that every agreement which transfers the title of a piece of land has to provable by a deed made by and before PPAT (Officials Empowered to Draw up Land Certificates). The material requirement determines the fulfillment of the formal materials. If the material requirements are not fulfilled by the seller and buyer, the formal requirements cannot be fulfilled.